Using real-time biofeedback to alter running biomechanics: A randomized controlled trial - Morris, J. B.; Goss, D. L.; Miller, E. M.; Davis, I. S. (Translational Sports Medicine, 2020)
In this study, we assessed the effectiveness of a mobile feedback system on transitioning runners to a non-rearfoot strike (NRFS) pattern and prospectively compared injury incidence rates at one year between rearfoot strike (RFS) and NRFS runners. 128 RFS runners participated in a 2-hour training session to learn a NRFS pattern with 114 completing the 1-year follow-up. Participants were randomized into a control group (CON) with no additional training and a biofeedback group (BFG) where they received equipment to provide real-time biofeedback to augment the transition to a NRFS pattern. Foot strike patterns (FSP) were assessed at baseline, post-training, 6-months, and 1-year. Injury data were collected through weekly email surveys over one year. Eighty percent of runners demonstrated a NRFS pattern following the training session (91/114, P < .001). The percentage of NRFS runners remaining at the one-year follow-up decreased slightly in both groups, but was not significantly different between groups (CON = 69%, P = .29; BFG = 75%, P = .36). Injury rates were similar between RFS runners (37% injured) and NRFS runners (30% injured) after one year (P = .47). The relative risk for knee injury in RFS runners was 5.64 (95% CI: 1.90-16.8; P = .02). In conclusion, both groups had a significant number of participants transition to a NRFS immediately after training and maintain NRFS at the 1-year follow-up. However, compliance with the sensor in the BFG group was very poor due to limitations of the sensor. Regardless of FSP, runners experienced 1-year injury incidence rates between 30%-37%. RFS runners had nearly a six times greater risk for developing a knee injury than NRFS runners.